Trends in molecular epidemiology of drug-resistant tuberculosis in Republic of Karelia, Russian Federation. Issue 1 (December 2015) - Mokrousov, Igor; Vyazovaya, Anna; Solovieva, Natalia; Sunchalina, Tatiana; Markelov, Yuri; Chernyaeva, Ekaterina; Melnikova, Natalia; Dogonadze, Marine; Starkova, Daria; Vasilieva, Neliya; Gerasimova, Alena; Kononenko, Yulia; et al.
Abstract Background Russian Republic of Karelia is located at the Russian-Finnish border. It contains most of the historical Karelia land inhabited with autochthonous Karels and more recently migrated Russians. Although tuberculosis (TB) incidence in Karelia is decreasing, it remains high (45.8/100 000 in 2014) with the rate of multi-drug resistance (MDR) among newly diagnosed TB patients reaching 46.5 %. The study aimed to genetically characterizeMycobacterium tuberculosis isolates obtained at different time points from TB patients from Karelia to gain insight into the phylogeographic specificity of the circulating genotypes and to assess trends in evolution of drug resistant subpopulations. Methods The sample included 150 M. tuberculosis isolates: 78 isolated in 2013–2014 ("new" collection) and 72 isolated in 2006 ("old" collection). Drug susceptibility testing was done by the method of absolute concentrations. Spoligotyping was used to test genotype-specific markers of a Latin-American-Mediterranean (LAM) family and its sublineages as well as a Beijing B0/W148-cluster. Results The largest spoligotypes were SIT1 (Beijing family, n = 42) and SIT40 (T family, n = 5). Beijing family was the largest (n = 43) followed by T (n = 11), Ural (n = 10) and LAM (n = 8). Successful Russian clone, Beijing В0/W148, was identified in 15 (34.9 %) of 43 Beijing isolates; all В0/W148 isolates were drug-resistant. Seven of 8 LAM isolates belonged to the RD115/LAM-RUS branch, 1 - to the LAM RD174/RD-Rio sublineage. MDR was found in Beijing (32/43), Ural (3/10), and LAM (3/8). In contrast, all T isolates were pansusceptible. Comparison of drug resistant subgroups of the new and old collections showed an increasing prevalence of the B0/W148 clonal cluster, from 18.0 % (mainly polyresistant) in 2006 to 32.6 % in 2014 (mainly MDR and pre-XDR). The West–east increasing gradient is observed for the Ural genotype that may be defined a 'Russian' strain. In contrast, the spoligotype SIT40 of the T family appears to be a historical Karelian strain. Conclusions Circulation of the MDRM. tuberculosis isolates of the Beijing genotype and its B0/W148 cluster continues to critically influence the current situation with the MDR-TB control in northwestern Russia including the Republic of Karelia. Revealed phylogeographic patterns of some genotypes reflect a complex demographic history of Karelia within the course of the 20th century.